Pembuatan Produk Instan Minuman Herbal Bir Pletok - Alif, Hefni Henidar; Tiadeka, Pemta (Universitas Muhammadiyah Gresik, 2019)
Nowaday, people have more attention for their health. They think healthy food or drink came from herbal plant. There are many ways to cultivate plant until they are ready to be harvested. UPT Materia Medica Batu is one of unit that managing plant from cultivate, harvest, making herbal product and analyxing those product. Bir Pletok is one kind of drink that made from ginger, cinnamon,lemongrass,clove, cardamom and secang wood. This herbal drink is believed can imcrease body fit. The purpose of this study is to formulate an acceptable herbal drink as bir pletok. Bir pletok is preparated into two formula (formula I and formula II). The difference between those formula is composition of ginger and secang wood. Sensory analysis is done to determine the panel’s acceptance include colour, taste and aroma characteristic. The result of this research is showed that bir pletok with formula I is getting good colour and taste. It came from secang wood that given interested red colour and low quantity of ginger so giving good taste. There is 15 panelis that participated to Sensory analysis. It can be conclude that 26,6% panelis very liked bir pletok with formula II based on colour. Then 13,3% said very like bir pletok with formula II depend on aroma and taste. This bir pletok formula II is better served hot or cold.